Peran Orang Tua Dalam Membimbing Di Rumah Pada Pembelajaran Daring Bagi Siswa Kelas X IPS Di SMA Negeri 1 Sindue Selama Masa Pandemi Covid-19 - Suari, Alan; Nurvita (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2023)
This study aims to describe the role of parents in guiding at home online learning for class X IPS students at SMA Negeri 1 Sindue during the Covid-19 pandemic. This type of research is qualitative using a descriptive approach. The research subjects were 10 students of class X. IPS and parents of students consisting of 10 people as key informants. Methods of data collection using observation, interviews, and documentation. data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of the study show that the role of parents in encouraging children to study at home is very important during a pandemic where learning is carried out online. Parental involvement in encouraging children's learning enthusiasm must be increased. booster or motivator, namely to foster children's enthusiasm for learning during the online learning period so that children continue to want to study even at home. student learning motivation is very important, there is encouragement from parents in online learning that has been going well, despite the various difficulties and obstacles faced by parents in online learning, namely expensive quotas, not being able to fully accompany their children, not understanding the material, and not having the ability to operationalize smartphones.